1999
DOI: 10.1093/clinchem/45.10.1695
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Serum Tumor Marker Concentrations and Usefulness in Clinical Monitoring

Abstract: Only a few markers have been instrumental in the diagnosis of cancer. In contrast, tumor markers play a critical role in the monitoring of patients. The patient’s clinical status and response to treatment can be evaluated rapidly using the tumor marker half-life (t1/2) and the tumor marker doubling time (DT). This report reviews the interest of determining these kinetic parameters for prostate-specific antigen, human chorionic gonadotropin, α-fetoprotein, carcinoembryonic antigen, cancer antigen (CA) 125, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(54 citation statements)
references
References 116 publications
0
50
0
2
Order By: Relevance
“…CA 125 serum concentration is usually adopted to evaluate the clinical situation in ovarian cancer patients [2]. An approach to rapid evaluation of clinical response and monitoring, instead of using the coarse CA 125 serum concentration, is the determination of tumor marker kinetic parameters, associated with changes in its concentrations, such as half‐life ( t 1/2 ) and doubling time (DT) [3]. The rate of decline in CA 125 during primary chemotherapy has been an important independent prognostic factor in several multivariate analyses [2].…”
Section: Overall Survival For the Different Prognostic Group Concernimentioning
confidence: 99%
See 1 more Smart Citation
“…CA 125 serum concentration is usually adopted to evaluate the clinical situation in ovarian cancer patients [2]. An approach to rapid evaluation of clinical response and monitoring, instead of using the coarse CA 125 serum concentration, is the determination of tumor marker kinetic parameters, associated with changes in its concentrations, such as half‐life ( t 1/2 ) and doubling time (DT) [3]. The rate of decline in CA 125 during primary chemotherapy has been an important independent prognostic factor in several multivariate analyses [2].…”
Section: Overall Survival For the Different Prognostic Group Concernimentioning
confidence: 99%
“…The rate of decline in CA 125 during primary chemotherapy has been an important independent prognostic factor in several multivariate analyses [2]. Several studies report the greatest difference in progression rate, found at a t 1/2 of 20 days while the normal CA 125 half‐life value to be determined varied from 5 to 10 days [3,4].…”
Section: Overall Survival For the Different Prognostic Group Concernimentioning
confidence: 99%
“…It would be valuable to perform a prospective study to analyze the CEA response in patients with metastatic colorectal cancer, undergoing palliative chemotherapy, in order to address the predictive and prognostic importance of CEA in those on treatment. Tumor markers such as CA125 for ovarian cancer, PSA for hormone‐sensitive prostate cancer and alpha fetoprotein for testicular cancer are well established in monitoring patients on therapy 19–21,25,26 . Perhaps with more supporting data, CEA for metastatic colorectal cancer can be added to this list.…”
Section: Discussionmentioning
confidence: 99%
“…CA125 and estradiol (E2) concentrations were measured using electro‐chemiluminescence immunoassay. The upper normal level for CA125 was considered 35 U/mL as widely used in clinical practice .…”
Section: Methodsmentioning
confidence: 99%